Propagation of Annonaceous plants - Ferreira, Gisela [UNESP]; De-La-Cruz-Chacón, Iván; Fernandes Boaro, Carmen Silvia [UNESP]; Baron, Daniel; Pinto de Lemos, Eurico Eduardo (FapUNIFESP (SciELO), 2019)
This review aims to present advances in studies on the propagation of the Annonaceae species, which includes species of economic importance such as: soursop, custard apple, atemoya and cherimoya. In sexual propagation, advances are mainly related to a better understanding of the stages of seed development, dormancy mechanisms, and germination. In asexual propagation, compatibility studies between grafts and rootstocks are presented, focusing on the expression of genes involved in tissue formation. The cutting method is also discussed, which is another option for the propagation for this group of plants considered difficult to root, approaching endogenous and exogenous factors related to the subject, as well as management strategies that affect the success of this technique.
Propagação de Anonáceas
Keywords: Annonaceae; cutting; germination; grafting; seed dormancy